Project Work Based Modules Development on Construction and Building Utilities Subjects to Increase Student Learning Outcomes of Vocational High School - Fiolentin, Enggar; Kusnan, Kusnan; Suparji, Suparji; Rijanto, Tri (Universitas Malikussaleh, 2021)
This study aims to develop a Work-Based Modules project in Construction and Building Utilities subjects to increase student learning outcomes of State Vocational High School 1 Sidoarjo. And to analyze the feasibility of the module in terms of (1) validity; (2) practicality; (3) has a project work-based Modules; (4) student learning outcomes after being taught by project-based Modules. This development research was carried out based on the six stages of the development method. The instruments used in this study were: (1) Questionnaire. Syllabus, lesson plans, Student Worksheets (SW) & Assessment instruments to measure the validity of values; (2) Learning management observation sheet, observation sheet to measure practicality; (3) learning outcomes test to measure the effectiveness of learning devices. The research was conducted on class XI students with competency skills in Modeling Design and Building Information. The results showed that the project-based Modules that works on the subjects of Construction and Building Utilities developed is valid in terms of validity, Practical interms of practicality, and proven effective in terms of effectiveness. Mean while, the learning outcomes indicated that (1) the Cognitive learning outcomes of students whose learning using project-based Modules and SW were significantly higher than students using only SW; (2) the learning outcomes in the Affective domain for students whose learning uses project-based modules, is significantly higher than students who learn only using SW; and (3) the learning outcomes inthe Psychomotor domain of students whose learning uses project-based Modules are significantly higher than those of students who only using SW.